Counseling for stress urinary incontinence in the era of adverse publicity around mesh usage: Results from a large‐sample global survey. Issue 2 (7th September 2022) - Zilberlicht, Ariel; Karmakar, Debjyoti; Dwyer, Peter L.; Chan, Garson; Schierlitz, Lore
Abstract: Objective: To investigate doctors' opinions of the use of synthetic mesh for the treatment of stress urinary incontinence (SUI) and the effect on patient's attitude following recent adverse publicity and legal findings. Methods: Electronic survey approved by International Urogynecological Association (IUGA) and American Urogynecologic Society (AUGS), distributed to their members. Results: A total of 593 respondents completed the survey. The preferred initial surgical treatment for SUI was retropubic midurethral sling (MUS) (62%), followed by trans‐obturator MUS (19%), mini‐slings (10%), and then bulking agents (5%). Despite prolongation of consultation, most respondents (87%) believed that clinicians should provide a patient information leaflet (PIL) for their patients. However, only 70% of respondents were doing this. Most participants would use either the IUGA PIL or their institution PIL (61%). Only 8% felt that patients have a positive preconception of synthetic mesh for SUI. Eighty‐three per cent of respondents had not changed their recommendations for treatment and the consent process. A logistic regression model identified preferences of certain geographic areas as predictors of consenting practices. Conclusion: Despite the negative publicity and the current medicolegal litigation involving MUS for SUI treatment, the majority of respondents still prefer this as the initial surgical treatment. Most clinicians value PIL in the surgical consent process. Synopsis: An international survey circulated among gynecologists and urologists found the mid‐urethral sling is still the preferred surgical treatment for stress urinary incontinence despite negative publicity.